Numerical and experimental study on the effect of cab-extender on the flow characteristics of a tractor-trailer - Syed Mohamed Ali, Jaffar; Omar, Ashraf Al; Nasikin, Mohd Faiz Diuzzaman (Penerbit Akademia Baru, 2018)
The aerodynamic drag on trucks can be reduced by use of active and passive techniques. In this work a passive method of using a cab-extender that is attached to the rear of the tractor is attempted. This cab-extender will help in reducing the drag force that act on the truck by minimizing the gap between the tractor and trailer. In this study, a tractor-trailer model was fabricated and tested in a low speed wind tunnel for its aerodynamics characteristics and the effect of cab-extender was also studied. Later Solid Works CFD package was used to study numerically the effect of this cab-extender on the aerodynamics of the truck and the results were validated against the experimental results. Finally using CFD approach the best angle of the cab-extender was reported for minimum drag.